L’Armure de François Ier : histoires d’un présent diplomatique - Juliette Allix (Les Cahiers de l'École du Louvre)
In 1539, Ferdinand I commissioned an armour from the Innsbruck armourer Jörg Seusenhofer to give it to François I. In the end, the king of France did not receive this present, which experienced an eventful fate and is now in the Musée de l’Armée in Paris (G 117) and the Hofjagd- und Rüstkammer in Vienna (B 147). This Doppelküriss became a collector’s item, the incarnation of a royal figure, a European diplomatic issue, a trophy of war and was even considered an arm during the Second World War. The history of this armour sheds light on the way the life of an object can alter its nature and enrich one’s reading of it; it also examines the status accorded from the modern period to the present to the particular cultural heritage constituted by military objects.